Evidence of the occurrence of structural chromosome changes at the initial diploid diversification of the autopolyploid Turnera sidoides L. (Passifloraceae) complex - Roggero Luque, Juan Manuel (2015)
Turnera sidoides L. (x = 7) is an autopolyploid complex of obligate outcrossing perennial herbs. Includes five taxonomic subspecies and seven morphotypes in which different ploidy levels were found from diploid to octoploid. The particular karyotypical features of each subspecies remain independently from the ploidy level. In order to infer the chromosomal differentiation processes that occurred during the diversification of T. sidoides, chromosome complements of representative diploid populations of subspecies carnea, holosericea and four morphotypes of the subspecies pinnatifida were analysed in this work by chromosome banding using chromomycine A3 (CMA) and 4?,6-diaminio-2-phenylindole (DAPI) fluorochromes and by fluorescence in situ hybridization (FISH) with 45S and 5S rDNA probes. All morphotypes and subspecies analyzed showed CMA+/DAPI- bands associated to secondary constrictions. DAPI staining was uniform in all the chromosomes of the complements and no DAPI+ bands were detected. On the other hand, FISH experiments showed that, in all subspecies and morphotypes, the 45S ribosomal DNA loci were always consistent with the localization of CMA+/DAPI- bands associated with the secondary constrictions. The pattern of CMA/DAPI bands and 45S and 5S rDNA loci varied among the three subspecies analyzed. On the other hand, the pattern of FISH signals was conserved in the four analyzed morphotypes of the subspecies pinantifida. The results obtained in this work show that at least part of the chromosomal differentiation of the T. sidoides complex would have occurred at diploid level.